2018
DOI: 10.1038/s41598-018-21098-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expansion of Multipotent Progenitors from Human Trabecular Meshwork

Abstract: To expand multi-potent progenitors from human trabecular meshwork (TM), we have created a new optimized method on two-dimensional (2D) followed by three–dimensional (3D) Matrigel in modified embryonic stem cell medium supplemented with 5% fetal bovine serum (MESCM + 5% FBS). The expanded TM cells were small cuboidal cells expressing TM markers such as AQP1, MGP, CHI3L1, and AnkG, embryonic stem cell (ESC) markers such as Oct4, Sox2, Nanog, and ABCG2, and neural crest (NC) markers such as p75NTR, FOXD3, Sox9, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 42 publications
7
46
0
Order By: Relevance
“…In contrast, TM cells cultured in MESCM+5% FBS could be expanded to P8 with a total cell doubling of 16. Based on our experiment results, culture of TM cells in MESCM+5% FBS, not MESCM alone on 2D Matrigel is the best condition for their expansion TM cells can be isolated by collagenase and expanded on coated Matrigel in MESCM+5%FBS up to 7 passages with 16 cell doublings [1]. Immunostaining showed that these cells at the time of isolation (D0) expressed TM markers such as AQP1, CHI3L1, MGP and AnkGs [1], similar to what have been previously reported [22,23].…”
Section: Ivyspringsupporting
confidence: 84%
See 3 more Smart Citations
“…In contrast, TM cells cultured in MESCM+5% FBS could be expanded to P8 with a total cell doubling of 16. Based on our experiment results, culture of TM cells in MESCM+5% FBS, not MESCM alone on 2D Matrigel is the best condition for their expansion TM cells can be isolated by collagenase and expanded on coated Matrigel in MESCM+5%FBS up to 7 passages with 16 cell doublings [1]. Immunostaining showed that these cells at the time of isolation (D0) expressed TM markers such as AQP1, CHI3L1, MGP and AnkGs [1], similar to what have been previously reported [22,23].…”
Section: Ivyspringsupporting
confidence: 84%
“…Immunostaining showed that these cells at the time of isolation (D0) expressed TM markers such as AQP1, CHI3L1, MGP and AnkGs [1], similar to what have been previously reported [22,23]. Compared with that of the D0 cluster immediately isolated by collagenase, qRT-PCR revealed a significant decline in expression of these markers as well as ESC and NC markers by P2 cells [1], suggesting that 2D matrigel cannot retain their progenitor status. This conclusion was confirmed by qTR-PCR of TM cell markers, ESC and NC markers.…”
Section: Ivyspringsupporting
confidence: 81%
See 2 more Smart Citations
“…In fact, we found that TM cells did not express detectable keratocan transcripts by RT-real-time PCR and cannot be induced into keratocyte-like cells even after the cells were cultured in 3-D Matrigel. 53 All Du's findings were that TM cells could be induced into adipose like cells. 62 Therefore, it is important to thoroughly characterize TM progenitors using TM cell markers, embryo stem cell markers, and neural crest progenitor markers.…”
Section: Tm Progenitorsmentioning
confidence: 99%